Methodological Foundations for the Development of Technology on the Basis of Innovative Approaches (Texas Journal of Engineering and Technology, 2024)
This scientific thesis explores the methodological foundations for the development of technology based on innovative approaches. The rapid advancements in technology and the increasing demand for innovative solutions have necessitated the development of robust methodologies that can effectively guide the process of technological innovation. This thesis aims to provide a comprehensive analysis of the key methodological principles, frameworks, and strategies that underpin the successful development of technology using innovative approaches. By examining case studies and drawing insights from existing literature, this research seeks to contribute to a deeper understanding of the methodological foundations that drive technological innovation